Adaptation of the 6D Gamification Model in a Software Development Course (2019)
This article shows a theoretical adaptation of the 6D gamification model, originally designed to be applied in marketing. The model establishes six steps that must be considered when applying gamification, in order to design the activity in which the game elements are going to be used. Each of these steps are described in a general way and considering how it can be applied in an educational context, specifically in the teaching of software development